Psychiatric Education for Pediatric Emergency Medicine Fellows: Should We be Doing More?. Issue 2 (February 2022) - Rudloff, James; Wurster Ovalle, Victoria; Barzman, Drew; Gonzalez-del-Rey, Javier
Objectives: N/A: The number of psychiatric encounters is steadily increasing across all pediatric emergency departments. Based on this growing national crisis, we hypothesized there is a lack of robust education in behavioral/mental health emergencies during pediatric emergency medicine (PEM) fellowship. Methods: This was a cross-sectional survey of PEM fellowship directors. The survey was submitted to the Pediatric Emergency Medicine Program Director Survey Committee via REDCap to all 83 fellowship directors. Results: Fifty-five (66%) PEM fellowship directors completed the survey from September 2019 to December 2019. Forty-three (78%) programs provide some type of didactic teaching, although only 7 (13%) programs offer more than 5 hours of didactics over 3 years of fellowship. Six (11%) programs offer electronic resources, 13 (24%) offer simulations in psychiatry, and only 4 (7%) programs require any type of psychiatry rotation. Forty-six (84%) programs do not currently use psychiatric emergencies as a competency for evaluating PEM fellows. Program directors felt significantly more confident in faculty than graduating fellows in the management of numerous diagnoses including agitation ( P < 0.001), homicidal ideation ( P = 0.044), neuroleptic malignant syndrome ( P = 0.006), acute dystonia ( P < 0.001), and heroin overdose ( P = 0.022). Ninety-six percent felt online curricula would be helpful to address this knowledge gap. Conclusions: Despite growing behavioral/mental health needs in the pediatric emergency department, there continues to be opportunity to improve psychiatric education during PEM fellowship. Program directors felt more confident in faculty than graduating fellows with several psychiatric diagnoses. Pediatric emergency medicine fellowship directors expressed a strong interest in online tools to assist in the education of PEM fellows.